Radio waves, children's rights and community communication: A radio for children's rights project in Africa. (1st March 2019) - Shule, Vicensia; Boothby, Hugo; Ahmed, Samah; Hansen, Anders Høg
This article draws upon research done as part of a formative evaluation of a radio project on children's rights in Tanzania. Fieldwork was conducted etween January and June 2016 followed by a longer period of analysis. In this article we take the project as a case study of applied Communication for Development (ComDev) and examine the insights it offers into this field of both theory and practice. Making use of data generated during the evaluation process we reflect critically on the project, and the evaluation processes itself, taking participation, community radio, selection, involvement, community exchange and radio practice as our points of departure. The empirical work and analysis revealed a strong potential in the project's activation of crucial local contexts and webs of communication, but also vulnerability and uncertainty in terms of vision as well as practical models for a sustainable continuation and impact.